Micro thrust measurement experiment and pressure field evolution of bionic robotic fish with harmonic actuation of macro fiber composites. (15th May 2021) - Hu, Dongyi; Lou, Junqiang; Chen, Tehuan; Yang, Yiling; Xu, Chao; Chen, Hairong; Cui, Yuguo
Graphical abstract: Pressure contour distribution and evolution around the robotic fish in different cases. Highlights: A micro thrust measurement system based on a decoupled lever mechanism is proposed. Pressure field distributions associated with the thrust variation are visualized. The MFC-actuated fish obtains a maximum mean thrust with a greatest oscillating velocity. The maximum instant drag first decreases, and then increases as the frequency increases. Variation of the thrust pattern/oscillating period reverse to the maximum instant drag. Abstract: The design and realization of underwater bionic robots actuated by smart materials have attracted growing attention in recent years. The experimental acquisition of the dynamic thrust force is crucial for the development of underwater robots. A simple micro thrust measurement system based on a decoupled lever mechanism is designed for a macro fiber composite (MFC)-actuated bionic robotic fish. The pressure field distribution and evolution associated with the thrust variation induced by the oscillating caudal fin of the robotic fish are visualized using computational fluid dynamics (CFD) technologies. A miniature MFC-actuated robotic fish that mimics the koi fish is designed. A simple decoupled lever mechanism with excellent linearity, high precision and resolution, and the ability to minimize the interference from the lateral force is proposed. Calibration results indicate that the output sensitivity of the designed measurement apparatus is 5.48 mN/V. The dynamic variations in the micro thrust generated by the robotic fish at different actuation levels are effectively captured using the proposed measurement system. Experimental results show that the MFC-actuated robotic fish obtains a maximum mean thrust of −2.95 mN in the case of the greatest tip oscillating velocity, which is consistent with Lighthill's elongated-body theory. Moreover, for the robotic fish, the maximum instant thrust grows with an increase in the oscillating frequency. The maximum instant drag first decreases, and then increases as the actuation frequency increases. It reaches its minimum value of 0.37 mN in the case of the maximum oscillating velocity. In contrast, the variation behavior of the thrust pattern/oscillating period is the reverse to that of the maximum instant drag, and it obtains a maximum of 85.7%. The propulsion performance indexes of the robotic fish in the CFD simulations match those of experimental results for different oscillating cases. Furthermore, the distribution and evolution mechanisms of the steady pressure fields around the oscillating robotic fish are revealed. The CFD simulations demonstrate that the variations in the instant thrust could be fully determined by the distributions and intensities of the concentrated pressure regions induced by the oscillating caudal fin. The cycle-averaged velocity fields around the caudal fin are closely related to the mean thrust generated by the MFC-actuated robotic fish. Accordingly, these results may be helpful in the development of underwater bionic robots actuated by smart actuators.